2005
DOI: 10.1016/j.femsim.2005.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Brucella melitensisinfection associated with Guillain–Barré syndrome through molecular mimicry of host structures

Abstract: Brucella melitensis is a facultative intracellular bacterium that can survive inside macrophages and the causative agent of brucellosis. In the present study, we found that a lipooligosaccharide of B. melitensis has a GM1 ganglioside-like structure and shows a strong antibody response in mice. The cholera toxin B subunit, which binds to GM1 ganglioside specifically, reacted with the surface of B. melitensis. Immunization with B. melitensis induced the production of anti-GM1 ganglioside antibodies in mice and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 45 publications
2
20
0
2
Order By: Relevance
“…In addition, cross-reactivity of antibodies to asialo-GM2 and LOS of a C. jejuni strain from a GBS patient has been demonstrated (26). Interestingly, Watanabe et al (86) reported that an LPS of Brucella melitensis had a GM1 ganglioside-like structure and that B. melitensis is a new etiological agent for GBS. Immunization of mice with B. melitensis induced mice to show flaccid limb weakness and ataxia-like symptoms that may be due to molecular mimicry between B. melitensis LPS containing GM1 ganglioside-like structures and peripheral nerve gangliosides.…”
Section: Oligosaccharides Of Lpss That Mimic Ganglioside Structuresmentioning
confidence: 99%
“…In addition, cross-reactivity of antibodies to asialo-GM2 and LOS of a C. jejuni strain from a GBS patient has been demonstrated (26). Interestingly, Watanabe et al (86) reported that an LPS of Brucella melitensis had a GM1 ganglioside-like structure and that B. melitensis is a new etiological agent for GBS. Immunization of mice with B. melitensis induced mice to show flaccid limb weakness and ataxia-like symptoms that may be due to molecular mimicry between B. melitensis LPS containing GM1 ganglioside-like structures and peripheral nerve gangliosides.…”
Section: Oligosaccharides Of Lpss That Mimic Ganglioside Structuresmentioning
confidence: 99%
“…A study investigating a brucellosis patient with GBS suggested that antibodies against gangliosides were responsible for the pathogenesis of peripheral nerve involvement. This study found that GM1 ganglioside antibodies were produced against molecules similar to gangliosides expressed on the surface of B.melitensis and caused symptoms similar to weakness in extremities and ataxia in rats [18]. As a result, it was proposed that polyradiculopathies related to brucellosis may cause nerve damage due to the antibody response to similarities between GM1 ganglioside molecules in peripheral nerves and Brucella spp.…”
Section: Discussionmentioning
confidence: 95%
“…As a result, it was proposed that polyradiculopathies related to brucellosis may cause nerve damage due to the antibody response to similarities between GM1 ganglioside molecules in peripheral nerves and Brucella spp. lipooligosaccharides [16,18]. Studies indicate that systemic treatment of brucellosis has caused regression of peripheral neuropathy linked to Brucella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, immunization with B. melitensis, induced the production of anti-GM1 gangeliosides antibodies that resulted in flaccid weakness and ataxia-like symptoms. 11 Cross-reactive immunological responses as a result of this molecular mimicry between Brucella lipooligosaccharide and GM1 gangeliosides may explain the acute axonal polyradiculopathy in Brucella infection.…”
Section: Discussionmentioning
confidence: 99%